SYNTHESIS OF SILVER NANOPARTICLES AND THEIR INFLUENCE ON THE FLUORESCENCE AND ABSORPTION OF ANTHRACENE - Yusupova, Zh.B. (Eurasian Physical Technical Journal, 2025)
The synthesis process of island silver films was investigated, with a focus on the role of solution pH as a key parameter for successful film formation. It was determined that the optimal pH for effective synthesis is 8. The results of particle distribution analysis by Feret diameter, performed using the ImageJ software, are also presented. The distribution histogram confirmed that the chemically deposited film is of high quality. The developed synthesis method enables the fabrication of silver nanoparticle films with tailored properties. The influence of the synthesized silver films on the luminescent properties of anthracene was studied, highlighting their potential applications in photonics and sensor technologies.